2002
DOI: 10.1080/02724980143000631
|View full text |Cite
|
Sign up to set email alerts
|

Authorship effects in the prediction of handwriting strokes: Evidence for action simulation during action perception

Abstract: Does the action system contribute to action perception? Recent evidence suggests that actions are simulated while being observed. Given that the planning and simulating system are the same only when one observes one's own actions, it might be easier to predict the future outcomes of actions when one has carried them out oneself earlier on. In order to test this hypothesis, three experiments were conducted in which participants observed parts of earlier self- and other-produced trajectories and judged whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 48 publications
4
80
0
1
Order By: Relevance
“…16 Knoblich and Flach (2001) found that when watching video clips representing an arm throwing a dart toward a target, participants were better at predicting the outcome of a throw when the video clips were of their own arm, rather than of that of someone else. Similar results have been obtained for participants' predictions about whether or not a new stroke will follow a dynamically presented handwritten symbol (Knoblich, Seigerschmidt, Flach, & Prinz, 2002).…”
Section: Motor Competence In Perceptionsupporting
confidence: 71%
“…16 Knoblich and Flach (2001) found that when watching video clips representing an arm throwing a dart toward a target, participants were better at predicting the outcome of a throw when the video clips were of their own arm, rather than of that of someone else. Similar results have been obtained for participants' predictions about whether or not a new stroke will follow a dynamically presented handwritten symbol (Knoblich, Seigerschmidt, Flach, & Prinz, 2002).…”
Section: Motor Competence In Perceptionsupporting
confidence: 71%
“…Most of the data on mirror neurons has been collected in allocentric third person conditions. However, it has been proposed that when one perceives one's own actions, there is a closer match between the predicted and actual outcomes of the action than when we perceive the actions of others (Knoblich, Seigerschmidt, Flach, & Prinz, 2002). Therefore, it could be expected that in motor-visual priming the first person perspective would show stronger effects than the third person perspective, and this was indeed the case.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have suggested that motor activation during action observation is higher for actions viewed from a spatial perspective which is compatible rather than incompatible with the actor's perspective (Alaerts et al, 2009;Maeda et al, 2002;Urgesi et al, 2006b). Furthermore, observers are more accurate in perceptual predictions for videos showing self-produced actions than for videos showing similar actions produced by other individuals (Knoblich & Flach, 2001;Knoblich, Seigerschmidt, Flach, & Prinz, 2002). In keeping with the notion that observed actions are perceived using internal models of the sensory consequences of executed actions (Hommel et al, 2001;Prinz, 1997), these results suggest that action prediction is maximally facilitated for close match between predicted and actual action outcomes like in the case of actions that are self-produced or belonging to the observers' motor repertoire.…”
Section: Aims Of the Present Studymentioning
confidence: 96%